Some problems of mass-transfer in binary mixtures in terms of diffusion model - L. A. Serafimov; A. V. Anisimov; K. Yu. Tarkhov (Тонкие химические технологии, 2009)
The analysis of mass-transfer equations used in practice of mass-exchange apparatus calculation for binary mixtures is carried out. It is showed that these equations are approximate. The accurate equation of mass-transfer based on diffusion model using linearization is proposed for qualitative investigations of binary mixtures rectification process